Networking imaginaries 2: multi-scalar networked learning for research and public pedagogies - Wilson, Anna (Proceedings of the International Conference on Networked Learning, 2026)
The world faces a variety of complex problems and predicaments (Thomas, Williams and Zalasiewicz, 2020) where decisions across all scales that we make now may have profound, unpredictable and/or irreversible consequences. Examples include climate change and biodiversity loss; rapid development and diffusion of generative AI; the decarbonisation of energy, transport and industry; challenges around land use; and challenges around migration. These are multi-scalar, global and highly localised. They have in common that they involve heterogeneous networks or assemblages of humans, non-humans, landscapes, technologies and infrastructures, entangling social, environmental and technological dynamics. In this paper, I suggest that networked learning can offer both a research methodology for studying these problems and a potential form of public pedagogy that may be useful in finding ways to reframe public debate about and understanding of their nature and consequences. To illustrate my position, I describe the processes and findings associated with a recent project exploring imagined futures in which carbon capture (use) and storage (CC(U)S) has been implemented as a way of mitigating greenhouse gas emissions and so tackling climate change. The project developed place-based participatory speculative fiction as a means of encouraging adults living and working in a range of sectors and places (mostly in Scotland) that are likely to be involved in and so affected by CC(U)S. I consider how learning emerges across a range of multi-scalar networks, and how echoes between the morphologies and topologies of these networks can help generate insights that may be used to inform future public pedagogies.